The Banda Geosyncline during Permian Time: A Paleogeographic Synthesis - S. Sartono (Journal of Mathematical and Fundamental Sciences, 1961)
In the eastern part of Indonesia a semicular zone known as the Banda Geosyncline coincides with the Outer Banda Arch. This geosynclines persisted from pre-Permian time until the Upper Tertiary. Its maximum extension was attained during Mesozoic time as shown by Mesozoic rocks of the many islands of the arch.The Banda Geosyncline was in existence during Permian time in an area which now occupies the southeastern corner of Indonesia as recorded by Permian rocks found on the islands of Savu, Roti, Timor, Leti, Luang and Babar. Reports of questionable Permian deposits on the islands of Ambon and in the eastern arm of island of Sulawesi (Celebes) may indicate that Permian geosynclines extended even further.Probably the Banda Geosyncline was already in existence in Carboniferous time. Carboniferous fossils are reported from southeastern Indonesia from the island of Leti and in the Tokala Mountains of the eastern arm of Sulawesi. The Carboniferous basin may form the initial stage of the Banda Geosyncline.The Permian Banda Geosyncline bordered a land mass which included the eastern part of Sulawesi, the Sula Spur, southern part of Irian (New Guinea), the Sahul shelf, and extended further to the south into Australia and Tasmania. The trend of geosynclines follows the present geanticlinal ridge of the islands of the Outer Banda Arch. The present Banda Sea apparently was an open sea during the Permian period.The distribution of Permian rocks and overthrust  units in Timor suggests that the Permian geosynclines in the southeastern corner of Indonesia was formed by two almost parallel basins, i.e. the Sonnebait-Mutis basin in the north and the Kekneno basin in the south. These two basins trended approximately northeast-southwest parallel with the trend of geosynclines in this part of Indonesia. The basins were separated by a narrow ridge responsible for the different facies of the sediments deposited in the two basins.The neritic volcanic rocks of the Sonnebait and the Mutis overthrust units indicate that the Sonnebait-Mutis depositional basin was deeper than Keknone basinof flysch facies. The rocks of the Kekneno basin were products of erosion and denudation of that part of the Permian land mass to the south. An abundance of fossils in the Sonnebait overthrust unit indicates favourable life conditions. Probably this basin had a good circulation with the open sea to the north, in the vicinity of present Banda Sea,At times volcano ejected tuffs and extruded lavas over the floor of Sonnebait-Mutis basin. The location of the vents has not been determined. The stratigraphical position and the character of the Mutis overthrust unit in Timor may give an indication that the volcanoes were located in the north of the Kekneno basin.Geographically the volcanic centra belonged to the afore mentioned Permian land mass. This continent had a bay which faced to the west into the present Banda sea.